Dancing hands : how Teresa Carreno played the piano for President Lincoln - Engle, Margarita (Atheneum Books for Young Readers, 2019)
Looks at the life and accomplishments of Teresa Carreno, one of the world's most famous pianists who, by age nine, performed for President Abraham Lincoln at the White House.